Parents’ perceptions of teachers’ support in a Japanese private kindergarten: overview of the trust relationship-building process - Eishin Teraoka; Miwako Okamoto; Taeko Saito; Hiroko Ube (Cogent Education)
This study explores the evolving role of early childhood education institutions in Japan, specifically kindergartens, in supporting parents amidst changing family dynamics. Despite policy mandates, the specific nature of parent-teacher relationships and their impact on parental support remains unclear. This research aims to clarify how trust develops between parents and teachers through daily interactions and its influence on parental support perceptions. A qualitative approach was adopted, using semi-structured interviews with 12 mothers from a private kindergarten in Tokyo. Codebook thematic analysis identified themes related to trust in parent-teacher interactions. As a result, three main themes emerged: predictability, dependability, and faith. Predictability refers to parents valuing consistent communication from teachers, fostering reliability. Dependability is reinforced by teachers’ responsiveness, professional competence, and comprehensive support from the kindergarten staff. Faith highlights emotional connections between children and teachers, demonstrated through empathy, individualised attention, and shared emotional experiences. This study enhanced the understanding of how trust develops in parent-teacher relationships and highlights its role in shaping effective partnerships in early childhood education.